2004
DOI: 10.1161/01.cir.0000111517.69230.0f
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Calcified and Noncalcified Coronary Atherosclerotic Plaque by Contrast-Enhanced, Submillimeter Multidetector Spiral Computed Tomography

Abstract: Background-We investigated the ability of multidetector spiral computed tomography (MDCT) to detect atherosclerotic plaque in nonstenotic coronary arteries. Methods and Results-In 22 patients without significant coronary stenoses, contrast-enhanced MDCT (0.75-mm collimation, 420-ms rotation) and intravascular ultrasound (IVUS) of one coronary artery were performed. A total of 83 coronary segments were imaged by IVUS (left main, 19; left anterior descending, 51; left circumflex, 4; right coronary, 9). MDCT data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
308
0
12

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 754 publications
(329 citation statements)
references
References 11 publications
9
308
0
12
Order By: Relevance
“…Coronary 64-slice multidetector computed tomography (MDCT) is a novel non-invasive imaging technology that now permits visualization of the coronary arteries and has been shown to detect both calcified and larger non-calcified coronary plaques in good agreement with intravascular ultrasound. (11)(12) In this study we sought to assess whether MS is associated with the presence and extent of both calcified and non-calcified coronary atherosclerotic plaque as detected by MDCT and whether this association is maintained after adjustment for other cardiovascular risk factors. …”
mentioning
confidence: 99%
“…Coronary 64-slice multidetector computed tomography (MDCT) is a novel non-invasive imaging technology that now permits visualization of the coronary arteries and has been shown to detect both calcified and larger non-calcified coronary plaques in good agreement with intravascular ultrasound. (11)(12) In this study we sought to assess whether MS is associated with the presence and extent of both calcified and non-calcified coronary atherosclerotic plaque as detected by MDCT and whether this association is maintained after adjustment for other cardiovascular risk factors. …”
mentioning
confidence: 99%
“…Improved temporal resolution, with scanning times in the order of 6 s, has also improved image quality by reducing potential fluctuations of heart rate during a single acquisition. Only two studies have compared assessment of plaque burden by 64-slice MDCT and IVUS (4,7), while a few others compared 16-slice MDCT with IVUS (6,15). Underestimation of plaque burden by MDCT was reported in three of four studies (4,6,7), and in all studies that actually reported plaque volumes (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies have compared assessment of plaque burden by 64-slice MDCT and IVUS (4,7), while a few others compared 16-slice MDCT with IVUS (6,15). Underestimation of plaque burden by MDCT was reported in three of four studies (4,6,7), and in all studies that actually reported plaque volumes (6,7). It is probable that motion artefacts were partly responsible for this underestimation by MDCT, even if scan times were 8 s to 11 s (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, it is important to note that a coronary angiotomography involves new methods and that great improvements are still required and hoped for. Nevertheless, documented In native coronaries, some authors have documented that the angio-CT is able to not only accurately detect lesions but also to classify the coronary plaque in accordance with its density and calcium content 14 . Schroeder et al 15 .…”
Section: Clinical Applicabilitymentioning
confidence: 99%